Dissociative ionization of H2 in an attosecond pulse train and delayed laser pulse - He, Feng; Thumm, Uwe (My University, 2010)
The ionization of H2 in a single attosecond extreme ultraviolet (XUV) pulse generates a nuclear wave packet in H2+, which is entangled with the emitted photoelectron wave packet. The nuclear wave-packet dynamics can be observed by dissociating H2+ in a delayed IR laser pulse. If H2 is ionized by a sequence of XUV pulses of an attosecond pulse train, whether or not the corresponding sequence of nuclear wave packets in H2+ is detected as a coherent or incoherent superposition depends on whether and how the photoelectrons are observed. We simulate the nuclear dynamics in this XUV-pump–IR-probe scenario and analyze our numerical results for both single attosecond pump pulses and pump-pulse trains of different lengths and temporal spacings between individual XUV pulses. By superimposing nuclear wave packets in H2+ generated by individual pulses in the pump-pulse train incoherently, we calculate proton kinetic energy release spectra that are in good qualitative agreement with the recent experiment of Kelkensberg et al. [Phys. Rev. Lett. 103, 123005 (2009)].